DEVELOPMENT MODEL OF LEARNING BASKETBALL BASED MODIFICATION GAMES FOR SECONDARY HIGH SCHOOL - Ahmad Hamidi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
The purpose of this research and development is to produce a model of learning basketball skills on learning physical education for students middle school first. In addition, this research and development is conducted to obtain information in depth about: development and application of learning model of bolabasket skill (hamidi) on basketball game for students of middle school first and know the effectiveness, efficiency and attractiveness of student to model made. This research and development use research & development (R & D) research method from borg and gall. The subjects in this research and development are the students of the first class VII students aged 13-14 years as many as 98 people. The instruments used in this research and development are questionnaires, questionnaires, battery test tests used to collect basic engineering skill data, as well as "game performance instrument test" instruments to collect data on students' basketball skills, as for stages in research and this development is, at the stage of: (1) needs analysis, (2) expert evaluation (initial product evaluation); (3) limited testing (small group trial); and (4) the main test (field testing). The model effectiveness test uses a battery test test to determine the level of mastery of students' basic basketball techniques and "GPAI tests" to find out the skill level of play. Data analysis technique used is "t-test" based on data analysis, for elementary technique aspect of students obtained the average value of pre test 29.86 and average post test 50.36, standard deviation pre test 5.5. and post test 6.0, value t -32.36 significance level 0.05 Because H0 is rejected means an increase in basic engineering capability. As for the skills to play based on data analysis using the test "t" obtained the average value of pre test 1.6 and average post test 3.83, standard deviation pre test 0.54 and post test 15.02, t value 0.085 significance level 0.05 Because H0 rejected means there is an increase in the ability of students' playing skills. Based on the data, it can be stated that basketball skill learning model for middle school first students is developed effectively and can improve basic technique skills and basketball playing skills of first medium school students. Keywords: Development, Game-based learning model, basic engineering skills, playing skills, basketball, students middle school first.